2012
DOI: 10.1002/hed.23153
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐xL protein: Predictor of complete tumor response in patients with oral cancer treated with curative radiotherapy

Abstract: Our study suggests that Bcl-xL expression along with clinical parameters may be useful for identifying patients with oral cancer likely to draw maximum benefit from curative radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Other molecular biomarkers including epidermal growth factor receptor (EGFR), B-cell lymphoma extra large (Bcl-xL), p53, and Ki67, have been shown to have prognostic significance i [3]. High EGFR expression has been correlated with poorer survival, while low levels of the anti-apoptotic protein, Bcl-xL, have been shown to be associated with improved response to radiation [4]. A recent study has suggested that elevated Ki67 levels may be associated with improved response to radiotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Other molecular biomarkers including epidermal growth factor receptor (EGFR), B-cell lymphoma extra large (Bcl-xL), p53, and Ki67, have been shown to have prognostic significance i [3]. High EGFR expression has been correlated with poorer survival, while low levels of the anti-apoptotic protein, Bcl-xL, have been shown to be associated with improved response to radiation [4]. A recent study has suggested that elevated Ki67 levels may be associated with improved response to radiotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of antiapoptotic BCL-2 family proteins, particularly MCL-1 has been reported in diverse human cancers including oral cancers [ 16 , 52 ]. We have earlier demonstrated that the prosurvival MCL-1 protein contributes to therapy resistance and poor prognosis in oral cancers and thus may prove to be a potential therapeutic target in OSCC [ 15 , 17 19 ]. Hence in the present study, we evaluated the efficacy of a BH3-mimetic pan-BCL-2 inhibitor Obatoclax against human oral cancer cell lines and also elucidated the mechanism of its action.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic dysregulation is believed to be one of the key underlying reason for the progression of OSCC [ 11 ]. BCL-2 and BCL-XL overexpression correlates with therapy resistance and poor prognosis in OSCC [ 12 15 ]. We have previously reported overexpression of anti-apoptotic members of the BCL-2 family, particularly MCL-1 (Myeloid Cell Leukemia-1) over their pro-apoptotic counterparts in human oral cancers [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Bcl-xL is very rarely mutated in human tumors, suggesting that putative key mutations within Bcl-xL would be unsuitable for cell proliferation and survival (see mutations and polymorphisms in S3 Fig ). Bcl-xL overexpression rather than mutation is associated with tumor development and poor treatment response in various cancers [ 35 – 41 ]. Indeed, tumor cells are believed to depend on, or are addicted to, anti-apoptotic Bcl-2 family members, including Bcl-xL [ 42 ], providing a selective advantage to cancer cells by allowing them to survive various stressful environments, cell stress phenotypes and/or cell death signals that directly ensue from oncogenic signaling, tumor suppressor deficiency or anticancer treatments [ 42 ].…”
Section: Discussionmentioning
confidence: 99%